Pengaruh Bahan Bakar Biodiesel dari Dimetil Ester Terhadap Kinerja Mesin Diesel Empat Langkah - Sitorus, Tulus Burhanuddin; Zebua, Yosua F.S.R; Sinaturi, Daniel F.B; Siagian, Jonathan A.R; -, Suprihatin; Siagian, Lestina (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2022)
This study aims to determine the effect of biodiesel fuel from dimethyl ester on four-stroke stationary diesel engines' performance and exhaust emissions. Tests were carried out using B10 and B30 fuels with engine speed variations and load variations without modifying the engine. The results showed that the torque, power, and thermal efficiency tended to decrease when using B10 and B30. In addition, the specific fuel consumption has increased when the engine uses B10 and B30. But exhaust emissions of CO and unburned hydrocarbon (UHC) decreased NOx and increased CO2 when the engine uses B10 and B30. This research also obtains the correlations and regression equations involving engine performance parameters.